Ratio of soil microbial biomass carbon to soil organic carbon in Himalayan rangeland - Limbu, Dil Kumar; Koirala, Madan (Himalayan Journal of Science and Technology, 2018)
The soil microbial biomass carbon to soil organic carbon ratio is a useful measure to monitor soil organic matter and serves as a sensitive index than soil organic carbon alone. Thus, the objective of this study is to identify and quantify the present status of ratio of soil microbial biomass carbon to soil organic carbon in Himalayan rangeland and to make recommendations for enhancing balance between microbial carbon and organic carbon of the soil. To meet the aforementioned objective, a field study was conducted from 2011 to 2013 following the Walkley-Black, Chromic acid wet oxidation method, and chloroform fumigation method for analysis of microbial carbon and organic carbon respectively. The study showed that the heavily grazed plot had significantly less value of ratio than occasionally grazed and ungrazed plots. The ratio was significantly high on legume seeding plot compared to nonlegume plot, but the ratio was independent of soil depth. Soil microbial biomass appeared to be more responsive than soil organic matter.